Ketamine infusion as a sedative-analgesic in severe ARDS (KISS) - Ramakanth Pata; Pagali Sandeep; Htun Min Aung; Meet J Patel; Tsering Dolkar; Nway Nway; Kosuru Bhanu; Abolfazl Ahmady; Roudabeh Kiani; Ramaiah Swaroop; Frances Schmidt; Danilo Enriquez (Greater Baltimore Medical Center, 2021)
Rationale Ketamine has been used as a sedative analgesic in trauma setting, but data regarding its efficacy and safety is lacking in severe ARDS. This retrospective study aims to determine if Ketamine is safer as a sedative agent in mechanically ventilated patients. During the COVID pandemic, as there was a shortage of sedative agents, Ketamine was used. Objectives The primary objective was to compare the safety of ketamine to other sedatives. The secondary objective was to compare the effect of ketamine to other sedatives regarding the need for vasopressor, incidence of delirium, infectious complications, acute kidney injury, hospital length of stay, and length of ventilator days. Methods A retrospective, observational cohort study was conducted. Measurements and Main Results One hundred and twenty-four patients (63 men and 61 women) were included. Thirty-four patients received ketamine, while 90 patients received other traditionally used sedatives such as propofol and midazolam. The patients' median age was 64 years in the ketamine group and 68 years in the non-ketamine group. Seventeen patients in the ketamine group (50%) and 65 patients (72%) in the non-ketamine group had mortality (p < 0.02). The hospital length of stay was 22.85 days (± 16.36) in the ketamine group and 15.62 days (± 14.63) in the non-ketamine group (p < 0.02). There was no statistically significant difference among the outcomes of the need for vasopressor, the incidence of delirium, infectious complications, and acute kidney injury. Conclusions Ketamine as a sedative-analgesic agent in COVID-19 patients with severe acute respiratory distress syndrome demonstrated safety with reduced mortality. The ketamine group had a higher hospital length of stay, but a similar complication profile compared to the non-ketamine group. Further prospective randomized controlled trials are warranted to confirm these findings.